Expression and prognosis analysis of PAQR5 in kidney cancer - Lu, Tao; Xu, Hai-rong; Dong, Wei; Dong, Hui (Frontiers in Oncology, 2022)
Progestin and adipoQ receptor 5 (PAQR5) affects the development of various malignancies and is specifically expressed in kidney. However, the role of PAQR5 in renal carcinoma remains unclear. We assessed the state of PAQR5 expression in kidney renal clear cell carcinoma (KIRC) by The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) datasets. Besides, immunohistochemistry (IHC) was performed to observe the expressions of PAQR5 protein in tumour tissues. The relationships between PAQR5 expression and clinical characteristics were investigated by UALCAN. Gene Expression Profiling Interactive Analysis (GEPIA) and Kaplan-Meier plotter were used to analyse the effect of PAQR5 expression levels on overall survival (OS) and relapse free survival (RFS). The relationships between clinical characteristics and survival were also evaluated by univariate and multifactorial Cox regression. Gene Ontology (GO) term analysis, Kyoto Encyclopedia of Genes and Genomes analysis (KEGG) and gene set enrichment analysis (GSEA) were performed on PAQR5 to explain the enrichment pathways and functions. Protein and protein interactions were explained by GeneMANIA and STRING. We also explored the relevance of PAQR5 to tumour immune cell infiltration and immunomodulatory molecules by TIMER and GEPIA. Finally, we explored the correlation of PAQR5 with the pathway proteins STATs, HIF-1α and mTOR using the GSE40435 dataset. PAQR5 expression was low in KIRC and correlated significantly with clinical characteristics including cancer stage, tumour grade and nodal metastasis status. Low PAQR5 expression was significantly associated with poorer survival. Cox regression analysis indicated that upregulation of PAQR5 was an independent factor for a good prognosis of KIRC. PAQR5 downregulation was associated mainly with STAT3 target upregulation, tumorigenesis and poor differentiation. PAQR5 expression also correlated positively with B cells, neutrophils, macrophages and dendritic cells and negatively with the infiltration of FOXP3+ Treg cells and the immune checkpoint molecules PD-1, CTLA4 and LAG3. Moreover, PAQR5 expression in KIRC was negatively correlated with the pathway proteins STAT1/2/3/4/5A, HIF-1α and mTOR. PAQR5 is an excellent predictor of KIRC prognosis and may be a potential molecular therapeutic target.